2012
DOI: 10.1590/s1516-05722012000100017
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of jasmonate and methyl jasmonate on a canine macrophage tumor cell line

Abstract: HERNANDES, C.; CARDOZO, G.P.; FRANÇA, S.C.; FACHIN, A.L.; MARINS, M.*; LOURENÇO, M.V.Universidade de Ribeirão Preto, UNAERP, CEP: 14096-900, Ribeirão Preto-Brasil *marins@heranza.com.br ABSTRACT: Cancer is one of the leading causes of death in dogs, a fact that has boosted the investigation for new more specific antitumor drugs. This study evaluated the antitumor activity of jasmonates in the canine macrophage cell line DH82 (ATCC # CRL-10389) isolated from a case of malignant histiocytoma. The activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Recently, Umukoro et al [118] found that MeJA exhibits specific anti-offensive aggressive activity, and they proposed this as a potential suitable treatment of reactive aggression in humans. Based on the promisingantitumor effects of JAs observed in animals, this molecule has been also proved as antitumor drugs for the treatment of canine oncologies [119,120]. Thus, there is evidences indicating that MeJA resulted in the highest inhibition of cell growth (82.2%), followed by doxorubicin (positive control, 80.7%) and JA (36.5%) of canine macrophage cell line DH82 (malignant histiocytoma) [120].…”
Section: Jas and Meja As Health Moleculesmentioning
confidence: 99%
“…Recently, Umukoro et al [118] found that MeJA exhibits specific anti-offensive aggressive activity, and they proposed this as a potential suitable treatment of reactive aggression in humans. Based on the promisingantitumor effects of JAs observed in animals, this molecule has been also proved as antitumor drugs for the treatment of canine oncologies [119,120]. Thus, there is evidences indicating that MeJA resulted in the highest inhibition of cell growth (82.2%), followed by doxorubicin (positive control, 80.7%) and JA (36.5%) of canine macrophage cell line DH82 (malignant histiocytoma) [120].…”
Section: Jas and Meja As Health Moleculesmentioning
confidence: 99%
“…The use of AJ and MJ in stimulation experiments is a widely used strategy to increase the production of secondary metabolites in vegetables (PERASSOLO et al, 2011), acting as a stress signal, activating the plant defense mechanism that is fundamental for production of biomolecules of pharmacological interest (HERNANDES et al, 2012, MIERSCH et al, 1989.…”
Section: Introductionmentioning
confidence: 99%